Non-simple elastic materials with double porosity structure - De Cicco, S. (Archives of Mechanics, 2022)
This paper is concerned with a strain gradient theory of elastic materials that have a double porosity structure. Firstly, we present the basic equations and the boundary conditions of the nonlinear theory. Then, we derive the equations of the linear theory and present the constitutive equations for chiral materials. The theory is applied to study the deformation of a chiral cylinder. The materials with a double porosity are of interest in geophysics and in mechanics of bone.